Regression model: choose the right one!!! / Zuraida Jaafar - Jaafar, Zuraida (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2021)
Regression analysis is a set of statistical methods used for the estimation of relationships between a dependent variable and one or more independent variables. It can be utilized to assess the strength of the relationship between variables and for modelling the future relationship between them. Regression analysis can be used to answer those questions such as: Do socio-economic status and race affect educational achievement? ●Do education and IQ affect earnings? ●Do exercise habits and diet affect weight? ●Are drinking coffee and smoking cigarettes related to mortality risk?